Evaluation of pro-inflammatory events induced by Bothrops alternatus snake venom. (1st February 2018) - Echeverría, Silvina; Leiguez, Elbio; Guijas, Carlos; do Nascimento, Neide Galvão; Acosta, Ofelia; Teixeira, Catarina; Leiva, Laura C.; Rodríguez, Juan Pablo
Abstract: Inflammation is a major local feature of envenomation by bothropic snakes being characterized by a prominent local edema, pain, and extensive swelling. There are reports demonstrating that whole Bothrops snake venoms and toxins isolated from them are able to activate macrophages functions, such as phagocytosis, production of reactive oxygen, cytokines and eicosanoids, however, little is known about the effects of Bothrops alternatus ( B.a. ) venom on macrophages. In this work, we evaluated the proinflammatory effects of B.a . venom with in vivo and in vitro experiments using the Raw 264.7 cell line and mouse peritoneal macrophages. We detected that B.a . venom augments cell permeability (2-fold), and cellular extravasation (mainly neutrophils), increase proinflammatory cytokines IL1 (∼300-fold), IL12 (∼200-fold), and TNFα (∼80-fold) liberation and induce the expression of enzymes related to lipid signaling, such as cPLA2α and COX-2. Additionally, using lipidomic techniques we detected that this venom produces a release of arachidonic acid (∼10 nMol/mg. Protein) and other fatty acids (16:0 and 18:1 n-9c). Although much of these findings were described in inflammatory processes induced by other bothropic venoms, here we demonstrate that B.a . venom also stimulates pro-inflammatory pathways involving lipid mediators of cell signaling. In this sense, lipidomics analysis of macrophages stimulated with B.a . venom evidenced that the main free fatty acids are implicated in the inflammatory response, and also demonstrated that this venom, is able to activate lipid metabolism even with a low content of PLA2 . Graphical abstract: Highlights: We describe the inflammatory response of B.a. venom using in vitro and in vivo assays. We detected that B.a. venom augments cell permeability, and cellular extravasation. B.a. venom release cytokines and induce the expression of cPLA2 and COX-2 enzymes. B.a. venom liberates arachidonic acid and other fatty acids from macrophages. This paper provides clues that will be useful for future pharmacological treatments.